2013
DOI: 10.1016/j.yjmcc.2013.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial nitric oxide signaling regulates Notch1 in aortic valve disease

Abstract: The mature aortic valve is composed of a structured trilaminar extracellular matrix that is interspersed with aortic valve interstitial cells (AVICs) and covered by endothelium. Dysfunction of the valvular endothelium initiates calcification of neighboring AVICs leading to calcific aortic valve disease (CAVD). The molecular mechanism by which endothelial cells communicate with AVICs and cause disease is not well understood. Using a co-culture assay, we show that endothelial cells secrete a signal to inhibit ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(173 citation statements)
references
References 39 publications
9
158
1
1
Order By: Relevance
“…Nos3 −/− and Notch1 +/− ;Nos3 +/− mice were bred to obtain Notch1 +/− ;Nos3 −/− mice (n=49) and littermate controls (n=216) and were genotyped, as described previously 20. For lineage‐specific deletions of Notch1 (using Tie2‐Cre,21 Mef2C‐Cre,22 Wnt1‐Cre23), Nos3 −/− ;Cre +/− male mice were bred with Notch1 flox/wt ;Nos3 +/− female mice to obtain Notch1 flox/wt ;Tie2‐Cre +/− ;Nos3 −/− (n=6) mice, Notch1 flox/wt ;Mef2C‐Cre +/− ;Nos3 −/− (n=7), Notch1 flox/wt ;Wnt1‐Cre +/− ;Nos3 −/− (n=4), and control littermates (n=4, n=4, n=4, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos3 −/− and Notch1 +/− ;Nos3 +/− mice were bred to obtain Notch1 +/− ;Nos3 −/− mice (n=49) and littermate controls (n=216) and were genotyped, as described previously 20. For lineage‐specific deletions of Notch1 (using Tie2‐Cre,21 Mef2C‐Cre,22 Wnt1‐Cre23), Nos3 −/− ;Cre +/− male mice were bred with Notch1 flox/wt ;Nos3 +/− female mice to obtain Notch1 flox/wt ;Tie2‐Cre +/− ;Nos3 −/− (n=6) mice, Notch1 flox/wt ;Mef2C‐Cre +/− ;Nos3 −/− (n=7), Notch1 flox/wt ;Wnt1‐Cre +/− ;Nos3 −/− (n=4), and control littermates (n=4, n=4, n=4, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…We previously described reduced survival to adulthood in Notch1 +/− ;Nos3 −/− mice, suggesting a potential embryonic phenotype 20. To further investigate the cause of this lethality, we bred Notch1 +/− ;Nos3 +/− female mice with Nos3 −/− male mice and examined the resultant litters.…”
Section: Introductionmentioning
confidence: 99%
“…13 NOTCH is the expected ligand for the DLL4 receptor, and there is a reported role for NOTCH signaling in VEC-VEC signaling, VIC-induced calcification, and valvulogenesis. 5,30 However, it is unclear if the same downstream pathways previously related to calcification and NOTCH are at play in this model. Further studies are needed to examine whether sustained angiogenic signaling leads towards valve calcification through angiogenetic-related cell-cell contact NOTCH inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…The molecular mechanism by which endothelial cells communicate with AVICs and cause disease is not well understood. Using a coculture and transwell assays, it was shown that a secreted signal from endothelial cells inhibits calcification of porcine AVICs [16]. Nitric oxide (NO), which is secreted by endothelial cells, is critical for numerous physiologic and pathologic processes and had been implicated in the process of aortic valve calcification.…”
Section: Notch1 Signaling and Aortic Valve Calcificationmentioning
confidence: 99%
“…Conversely, increased nuclear localization of NICD was noted with the addition of NO donor. Lastly, the NOS3 and Notch1 signaling pathways genetically interact in vivo as NOS3;Notch1 compound mutant mice display a highly penetrant aortic valve disease [16]. These mice have highly penetrant BAV and develop hemodynamically significant aortic valve stenosis and regurgitation.…”
Section: Notch1 Signaling and Aortic Valve Calcificationmentioning
confidence: 99%